2017
DOI: 10.1186/s12882-017-0684-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of Endophthalmitis in chronic dialysis patients: a 13-year experience in a tertiary referral center in Taiwan

Abstract: BackgroundEndophthalmitis is a severe eye infection leading to disabling outcome. Because there were only a few case report illustrating endophthalmitis in chronic dialysis patient, we would like to investigate the epidemiology and clinical features of endophthalmitis in chronic dialysis patient in a tertiary referral center.MethodsWe searched the health information system in the study hospital with ICD9 encoding endophthalmitis during Jan. 2002 to Dec. 2015. A total of 32 episodes of endophthalmitis occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Systemic treatment was recommended by all authors given the specific pathogeny of EE, and in some cases, it was the only therapy administered [ 41 , 45 ]. It should be started immediately after the blood samples for culture have been taken.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic treatment was recommended by all authors given the specific pathogeny of EE, and in some cases, it was the only therapy administered [ 41 , 45 ]. It should be started immediately after the blood samples for culture have been taken.…”
Section: Discussionmentioning
confidence: 99%
“…In 7 of 8 studies conducted in Southeast Asia, Gram-negative infections predominated (43.9% to 83.3% of patients) and K. pneumoniae was the most frequent microorganism (26.8% to 53% of patients) [ 6 , 12 , 17 , 30 , 41 – 44 ]. One exception was a study conducted in Taiwan on chronic dialysis patients, where Staphylococcus was the most frequent cause [ 45 ]. In two small series from Japan, the prevalent causes were Staphylococcus (57%) and Candida (30%) [ 6 , 46 ].…”
Section: Microbiological Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, in patients without DM, endophthalmitis may be caused by different pathogens, including more invasive microorganisms, such as methicillinresistant Staphylococcus aureus (MRSA), bacilli, and fungi, depending on the primary source of the infection. 2,4,16 In a review article, Han 17 discussed the association of hepatic abscess from K. pneumoniae with DM and septic endophthalmitis; the author concluded that septic endophthalmitis in patients with a liver abscess due to gram-negative organisms other than K. pneumoniae is associated with a poor outcome. 17 Therefore, management of these patients can be more difficult, resulting in a higher rate of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic infections complicate catheter-related bacteremia in 5-10% of cases, with endocarditis being the most frequent. EE is described as a rare metastatic infection, with few cases reported worldwide [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%